2009
DOI: 10.1103/physreva.79.042302
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death and sudden birth of entanglement in common structured reservoirs

Abstract: We study the exact entanglement dynamics of two qubits in a common structured reservoir. We demonstrate that, for certain classes of entangled states, entanglement sudden death occurs, while for certain initially factorized states, entanglement sudden birth takes place. The backaction of the non-Markovian reservoir is responsible for revivals of entanglement after sudden death has occurred, and also for periods of disentanglement following entanglement sudden birth.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
305
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(315 citation statements)
references
References 29 publications
8
305
2
Order By: Relevance
“…The SV and SR effects in such systems have different character than studied here. Mazzola et al [51] observed the oscillations in short times, which disappear after some finite time and are related to the non-Markovian character of the reservoirs. In contrast, in the examples presented here, the periodic behavior of the nonclassicality witnesses persists as being related to the unitary evolution of the states.…”
Section: Periodic Sudden Vanishing Of Nonclassicality Witnesses Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The SV and SR effects in such systems have different character than studied here. Mazzola et al [51] observed the oscillations in short times, which disappear after some finite time and are related to the non-Markovian character of the reservoirs. In contrast, in the examples presented here, the periodic behavior of the nonclassicality witnesses persists as being related to the unitary evolution of the states.…”
Section: Periodic Sudden Vanishing Of Nonclassicality Witnesses Fmentioning
confidence: 99%
“…V, should not be confused with the oscillations of the entanglement measures in systems interacting with non-Markovian reservoirs (see, e.g., Ref. [51]). The SV and SR effects in such systems have different character than studied here.…”
Section: Periodic Sudden Vanishing Of Nonclassicality Witnesses Fmentioning
confidence: 99%
“…Cavities provide a well-defined mode spectrum and a relatively loss-free environment such that the atom-field interactions can have anomalously large coupling strengths, leading to reversible, non-Markovian type dynamics of the system. As a consequence, the already dead entanglement can revive even if in the equivalent free-space situation no revival is predicted [11,12,23,[27][28][29][30][31][32][33]. However, calculations based on deriving the master equation for the reduced density operator of two atoms, both placed inside a cavity, frequently assume a large distance between the atoms such that there is no direct interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…This effect, known as sudden death of entanglement (SDE), has been studied in a numerous number of papers [2,[11][12][13][14][15], and has recently been observed in experiments involving photons [16,17] and atoms [18]. Furthermore, theoretical treatment of the coupling of sub-systems to a common (non-local) environment has predicted that the already destroyed entanglement could suddenly revive [19][20][21][22][23] or initially separable systems could become entangled after a finite time, the phenomenon known as sudden birth of entanglement (SBE).…”
Section: Introductionmentioning
confidence: 99%
“…In non-Markovian (NM) case, S is coherently interacting with a finite part of B over a finite time. From different theoretical efforts [4][5][6][7][8][9][10] we distill a central question: how can we divide the environment B into the memory M and detector D? Part M is continuously entangled with S but the compound S+M becomes a Markovian open system, as we shall argue.…”
mentioning
confidence: 99%